2014
DOI: 10.1038/npp.2014.145
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Atrophy in Major Depression: a Function of Childhood Maltreatment Rather than Diagnosis?

Abstract: Reduced hippocampal volumes are probably the most frequently reported structural neuroimaging finding associated with major depressive disorder (MDD). However, it remains unclear whether altered hippocampal structure represents a risk factor for or a consequence of MDD. Reduced hippocampal volumes were consistently reported in subjects affected by childhood maltreatment. As the prevalence of childhood maltreatment is highly elevated in MDD populations, previous morphometric findings regarding hippocampal atrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 44 publications
14
110
0
7
Order By: Relevance
“…To assess the influence of psychopharmacological therapy in the MDD sample, medication load was coded in terms of dose and treatment durations into levels 1-4 according to the suggestions of Sackeim 14 and as conducted previously by our group and others. [15][16][17] To be included, patients with MDD had to be free from psychotic symptoms according to the SCID-I. 13 We assessed family history of depression in the MDD-FH+, the MDD-FH-and the HC-FH-samples via familial anamnesis.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the influence of psychopharmacological therapy in the MDD sample, medication load was coded in terms of dose and treatment durations into levels 1-4 according to the suggestions of Sackeim 14 and as conducted previously by our group and others. [15][16][17] To be included, patients with MDD had to be free from psychotic symptoms according to the SCID-I. 13 We assessed family history of depression in the MDD-FH+, the MDD-FH-and the HC-FH-samples via familial anamnesis.…”
Section: Participantsmentioning
confidence: 99%
“…This was performed by means of the AlphaSim procedure, which accounted for spatial correlations between grey matter values in neighbouring voxels, implemented in the REST toolbox (http://restfmri.net/forum/index.php). 16,[29][30][31] The cluster threshold calculation was based on a residual smoothness value of 10 mm FWHM, as estimated with SPM8. The empirically determined cluster threshold was k = 26 voxels for the medial OFC and k = 40 voxels for the bilateral DLPFC.…”
Section: Second-level Analysesmentioning
confidence: 99%
“…Other VBM studies have also found structural abnormalities in regions including the insula, thalamus, and hippocampus in MDD patients [28,[35][36][37][38][39][40][41][42][43]. The anterior insula connects to the inferior frontal cortex and to the ACC [44].…”
Section: Mr Imaging Of Brain Morphology and Structurementioning
confidence: 95%
“…The hippocampus is functionally important for long-term memory storage of episodic events as well as emotion and mood regulation [69]. A number of studies have linked hippocampal abnormalities with early life stress and depression [70][71][72][73]. Evidence suggests 5-HTTLPR may play an important role in explaining this relationship.…”
Section: The Role Of Affective Functioningmentioning
confidence: 99%